Spatiotemporal Dynamics of Pro-Inflammatory Mediator Expression in Pelteobagrus vachelli During Ichthyophthiriasis: A 40-Day Longitudinal Study of IL-1β, IL-6, and SAA - Yang He; Miaomiao Wang; Jun Wang; Yadong Wang; Xiaolan Pi; Qi Wang; Yan Fu; Wei Fan; Qian Yang (Animals)
Interleukin-1β (IL-1β), interleukin-6 (IL-6), and serum amyloid A (SAA) are key pro-inflammatory mediators in the regulation of immune responses. The hypothesis posits that their expression varies with the progression of Ichthyophthirius multifiliis (Ich) infection and may serve as predictors of disease outcome. To elucidate their spatiotemporal dynamics, the full-length CDS of IL-1β, IL-6, and SAA in Pelteobagrus vachelli were cloned, and then their mRNA levels were tracked from infection onset (day 0) to resolution (day 40) or mortality in seven tissues. Key findings revealed a surge in IL-1β expression in the kidney and SAA expression in the spleen at 5 days post-infection (dpi), coinciding with no visible symptoms. Significant SAA elevation in the head kidney was observed at 10 dpi, preceding the emergence of white spots on the skin. This was followed by gill-specific SAA downregulation at 20 dpi, when 40% of fish presented with white spots. Complete clinical resolution by 40 dpi correlated with reduced hepatic SAA and branchial IL-1β levels. Notably, the concurrent upregulation of all three mediators occurred exclusively in the skin of moribund individuals. These findings identify potential biomarkers for tracking host inflammatory responses in ichthyophthiriasis.